2014
DOI: 10.1186/1756-3305-7-71
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Plasmodium infection rates and insecticide susceptibility profiles between the sympatric sibling species Anopheles parensis and Anopheles funestus s.s: a potential challenge for malaria vector control in Uganda

Abstract: BackgroundAlthough the An. funestus group conceals one of the major malaria vectors in Africa, little is known about the dynamics of members of this group across the continent. Here, we investigated the species composition, infection rate and susceptibility to insecticides of this species group in Uganda.MethodsIndoor resting blood-fed Anopheles adult female mosquitoes were collected from 3 districts in Uganda. Mosquitoes morphologically belonging to the An. funestus group were identified to species by PCR. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(52 citation statements)
references
References 29 publications
5
46
1
Order By: Relevance
“…The finding of An. funestus populations being resistant to both pyrethroids and carbamates (bendiocarb and propoxur) in all the study areas is consistent with results reported from several other studies [17, 19, 24, 2628] except for Uganda [25, 29] where this species was susceptible to carbamates (bendiocarb). Furthermore, the results from Malawi confirm a regional decline in the susceptibility of malaria vectors to pyrethroid and carbamate insecticides [14].…”
Section: Discussionsupporting
confidence: 91%
“…The finding of An. funestus populations being resistant to both pyrethroids and carbamates (bendiocarb and propoxur) in all the study areas is consistent with results reported from several other studies [17, 19, 24, 2628] except for Uganda [25, 29] where this species was susceptible to carbamates (bendiocarb). Furthermore, the results from Malawi confirm a regional decline in the susceptibility of malaria vectors to pyrethroid and carbamate insecticides [14].…”
Section: Discussionsupporting
confidence: 91%
“…; Mulamba et al . ), (ii) the dramatic increase in the cyp‐l haplotype was coincident with the increase in ITN usage in 2006, and (iii) bioassay results confirm that kdr alone cannot account for the level of resistance observed for kdr:cyp‐l A. coluzzii genotype. That said, the nonsynonymous mutation in AGAP013173 and regulatory variation at Tailless or CPR125 should also be considered good candidates for selection.…”
Section: Discussionmentioning
confidence: 70%
“…Continued population sampling is needed to assess whether the cyp-l A. gambiae genotype detected in 2014 will be selected for in the population and warrant further study. We hypothesize that selection has acted upon cis-regulatory variation at CYP9K1 because (i) CYP9K1 has been shown to be upregulated in resistant anopheline mosquitoes (Tene et al 2013;Mulamba et al 2014), (ii) the dramatic increase in the cyp-l haplotype was coincident with the increase in ITN usage in 2006, and (iii) bioassay results confirm that kdr alone cannot account for the level of resistance observed for kdr:cyp-l A. coluzzii genotype. That said, the nonsynonymous mutation in AGAP013173 and regulatory variation at Tailless or CPR125 should also be considered good candidates for selection.…”
Section: Introgression Vs Selection On Standing Variationmentioning
confidence: 92%
See 1 more Smart Citation
“…However, this population was completely susceptible to bendiocarb (carbamate), malathion (organophosphate) and dieldrin. Recently, widespread resistance against pyrethroids and DDT was observed across Uganda [53,61]. Mutations which confer resistance to DDT and pyrethroids, West African (L1014F) and East African (L1014S) mutations, have been reported from the Ugandan An.…”
Section: Ugandamentioning
confidence: 99%